The Palestinians’ Quest for Justice at the ICJ: The UNSC as a Stumbling Block? - Hassan, Fareed Mohd; Sabaruddin, Nurul Azyani Zafirah; Yuliantiningsih, Aryuni; Arafat, Muhammad Rusli; Mega Jaya, Belardo Prasetya (Brawijaya Law Journal, 2024)
Human rights abuses occurring in Gaza, including civilian casualties, have been countlessly reported. Despite numerous resolutions presented, particularly to the United Nations (UN) Security Council (UNSC), data from the UN reveals that they have unfortunately been vetoed. South Africa initiated a legal action before the International Court of Justice (ICJ) accusing Israel of breaching the 1948 Genocide Convention—a treaty to which both nations are Parties to. Based on doctrinal analysis, this paper raises one big question; whether the UNSC, that is supposed to uphold international peace and security, will become a stumbling block in the quest for justice for the Palestinian and fails to serve its purpose? This paper argues that judging from Netanyahu’s statement that Israel will not follow and perform any ICJ’s decisions and the United States, being one of the UNSC permanent members will use any necessary measures within the UNSC to prevent such decision from being enforced. This paper concludes that the veto power within the UNSC hinders the pursuit of justice for the Palestinians and the ability of certain member states to veto resolutions creates challenges in the Council’s effectiveness and compromises its capacity to address the conflict for the pursuit of justice.